PENGABDIAN MASYARAKAT PADA UMKM SUSU KEDELAI JUWARA - Ni Putu Desy Damayanthi; I Gede Putu Adhitya Prayoga; I Gede Aditya Pramana; I Nyoman Angga Arditya (JURNAL PENGABDIAN MANDIRI, 2025)
Susu Kedelai Juwara is a micro, small, and medium enterprise (UMKM) focused on the production of soybean milk, located in West Denpasar. Established in 2020, this business emerged as a response to the challenges faced during the Covid-19 pandemic. In its two years of operation, Susu Kedelai Juwara has successfully developed six flavor variants. The business has been running for two years, operated by selling the products door-to-door using a motorcycle cart. They are offering its products at several strategic locations such as Suli streat, Diponogoro streat, and Teuku Umar streat. Although it has been operating well, Susu Kedelai Juwara faces challenges in packaging and marketing. Currently, their products are packaged in simple 500ml plastic bottles without labels, and promotion is conducted through the motorcycle cart and WhatsApp. With this strategy, they are able to sell around 70-80 bottles per day. To enhance the competitiveness and market value of the products, this community service activity aims to address the issues faced by Susu Kedelai Juwara. The plan includes improving the packaging to labeled plastic bottles and utilizing social media platforms such as Instagram and Facebook for more effective marketing. With these steps, it is hoped that Susu Kedelai Juwara can increase its visibility and sales in the market.